Paroxysmal Atrial Fibrillation Ablation Using a Novel Variable-Loop Biphasic Pulsed Field Ablation Catheter Integrated With a 3-Dimensional Mapping System: 1-Year Outcomes of the Multicenter inspIRE Study - Duytschaever, Mattias; De Potter, Tom; Grimaldi, Massimo; Anic, Ante; Vijgen, Johan; Neuzil, Petr; Van Herendael, Hugo; Verma, Atul; Skanes, Allan; Scherr, Daniel; Pürerfellner, Helmut; Rackauskas, Gediminas; et al. (Circulation. Arrhythmia and electrophysiology, 2023)
The inspIRE study (Study for Treatment of Paroxysmal Atrial Fibrillation [PAF] by Pulsed Field Ablation [PFA] System With Irreversible Electroporation [IRE]) evaluated safety and effectiveness of a fully integrated biphasic pulsed field ablation (PFA) system with a variable-loop circular catheter for the treatment of drug-refractory paroxysmal atrial fibrillation. Subjects underwent pulmonary vein (PV) isolation with the PFA system, using at least 12 applications per vein; adenosine/isoproterenol was administered to confirm entrance block. Wave I assessed initial safety, including for esophageal lesions, silent cerebral lesions, and PV stenosis. Wave II (pivotal phase) tested (1) primary safety, incidence of early-onset primary adverse events, and (2) primary effectiveness, confirmed PV isolation with freedom from documented atrial arrhythmia at 12 months. The study design specified an interim analysis to determine early success once 30 subjects reached the 12-month follow-up and all subjects reached 3-month follow-up. Across 13 centers in Europe/Canada, 226 subjects were enrolled, met criteria for safety and effectiveness evaluations, and received PFA (Wave I, 40; Wave II, 186). Wave I demonstrated no esophageal thermal lesions or PV stenosis. Among 39 subjects with cerebral magnetic resonance imaging, silent cerebral lesions were detected in 4 of the first 6 subjects, after which workflow enhancements, including a 10-second pause between PFA applications, were implemented; subsequently, only 4 of 33 subjects had silent cerebral lesions. In the Wave II phase, no primary adverse events were reported. Upon declaring early success, 83 subjects reached 12-month follow-up. With 100% entrance block, PV isolation without acute reconnection was achieved in 97.1% of targeted veins. For Wave II, the primary effectiveness end point per Kaplan-Meier at the time of interim analysis was 70.9%; 12-month freedom from symptomatic atrial fibrillation/atrial flutter/atrial tachycardia recurrence and repeat ablation was 78.9% and 92.3%, respectively. Total procedure and transpired PFA times were 70.1±27.7 and 26.7±14.0 minutes, respectively. The inspIRE trial confirmed the safety and effectiveness of the novel mapping-integrated PFA system. URL: https://www. gov; unique identifier: NCT04524364.